2019
DOI: 10.1590/0100-29452019446
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock-scion interaction:6. Phenology, chilling and heat requirements of Cabernet Sauvignon grapevine

Abstract: The grapevine phenology is dependent on several factors, such as genetics, soil characteristics, climate conditions, pests and diseases and vineyard cultural practices. Among these, grafting may have an effect on the scion behavior due to the influence of the rootstock. Therefore, an experiment was carried out for two years to determine the effect of rootstocks on Cabernet Sauvignon (CS) grapevine phenology, chilling and heat requirements. Treatments consisted of vines grafted on the rootstocks Rupestris du Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
3
1
Order By: Relevance
“…Climate alone does not explain all phenological variation as different grape cultivars grown under similar conditions still show large variations in the timing of different events [21]. The number of days and the GDD necessary to complete the growing cycle of these four varieties were close to the figures reported by authors but TN and TF can grow over wider range of thermal conditions that favors their adaptability to different climatic conditions [29,[49][50][51].…”
Section: Discussionsupporting
confidence: 66%
“…Climate alone does not explain all phenological variation as different grape cultivars grown under similar conditions still show large variations in the timing of different events [21]. The number of days and the GDD necessary to complete the growing cycle of these four varieties were close to the figures reported by authors but TN and TF can grow over wider range of thermal conditions that favors their adaptability to different climatic conditions [29,[49][50][51].…”
Section: Discussionsupporting
confidence: 66%
“…There was no significant effect of rootstocks on thermal demands in this study, but some authors claim that rootstocks can affect grapevines' thermal demands (Miele 2019;Tecchio et al 2019). Thus, grapevines required an average of 1,615.1 DD and 1,465.2 DD to complete the first and second production cycles, respectively (Table 2).…”
Section: Resultscontrasting
confidence: 58%
“…'IAC 571-6 Jundiaí' rootstocks, did not influence the phenology of 'SR 501-17' grapevine (Mattar et al 2019). However, several studies have reported that rootstock change the phenology of Vitis vinifera cultivars, such as Albarín Negro, Verdejo Negro, and Cabernet Sauvignon due to climate and soil adaptation in different regions (Loureiro et al 2016;Loureiro et al 2020;Miele 2019).…”
Section: Discussionmentioning
confidence: 90%